1991
DOI: 10.1128/jcm.29.7.1422-1428.1991
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the autoSCAN-W/A rapid bacterial identification system and the Vitek AutoMicrobic system for identification of gram-negative bacilli

Abstract: The autoSCAN-W/A (W/A; Baxter MicroScan, West Sacramento, Calif.) with the new fluorometric Rapid Neg Combo 1 (RNC) panel is a fully automated fluorometric system for identification of both enteric and nonenteric gram-negative bacilli within 2 h. We compared the W/A with the Vitek AutoMicrobic System (Vitek AMS; Vitek Systems, Inc., Hazelwood, Mo.) for identification of 383 clinical isolates of gram-negative bacilli. The API 20E (Analytab Products, Plainview, N.Y.) and conventional biochemical testing were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 16 publications
2
25
0
1
Order By: Relevance
“…Published evaluations exist for each of the four commercial systems evaluated in the present study (1,2,4,11,14,15,17,22,23). However, only one of those studies, the one by Kitch et al (11), specifically states if any of their study isolates were recovered from CF patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Published evaluations exist for each of the four commercial systems evaluated in the present study (1,2,4,11,14,15,17,22,23). However, only one of those studies, the one by Kitch et al (11), specifically states if any of their study isolates were recovered from CF patients.…”
Section: Discussionmentioning
confidence: 98%
“…Instead of not giving an identification for this organism, the system assigned an incorrect identification to eight of nine B. gladioli isolates, including five as B. cepacia. The Vitek card has been evaluated in several laboratories (14,15,17,22). However, only two studies have evaluated the system with multiple isolates of B. cepacia and related organisms.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent study of the GNI was reported by Pfaller et al (95). They tested 292 members of the family Enterobactenaceae and 91 nonenteric bacilli (including 8 genera and 11 species).…”
Section: Kitmentioning
confidence: 99%
“…In considering recent studies of the GNI, members of the family Enterobactenaceae were correctly identified in the range of 94.7 to 96.2%, with Enterobacter spp. the most frequently misidentified (24,95,120). Gram-negative organisms that were not members of the Enterobactenaceae were correctly identified in the range of 79.6 to 95%, with P. aeruginosa and Acinetobacter spp.…”
Section: Kitmentioning
confidence: 99%
“…While several studies have examined the performances of automated microbial identification systems for the examination of clinical isolates (11,18,(21)(22)(23)(24)(25)(26)(27)29), little work has been done to study the sensitivities and specificities of these systems for the testing of pathogens isolated from food samples. Many of the previous studies of clinical isolates were performed with versions of these automated microbial identification systems that contained now obsolete databases (11,14,18,25,28), and many of the studies did not include species that are often detected as pathogens in food samples.…”
mentioning
confidence: 99%